CASE STUDY OF USING THE DOMESTIC ANALOGUE OF CYCLOSPORINE A - V.A. Goryainov; M.M. Kaabak; N.N. Babenko; N.T. Vorob'eva; L.A. Shishlo; M.M. Morozova; T.Yu. Cheprasova (Union of pediatricians of Russia, 2010)
The article illustrates results of an important trial for the Russian pharmaceutical industry, an assessment of the efficacy and safety of domestic immunosuppressive medication Cyclosporine A. A comparative analysis was made of pharmacokinetics, hepato-, myelo- and renal toxicity of domestic Cyclosporine A and Novartis-manufactured Cyclosporine A in patients with a renal allotransplant. The authors convincingly demonstrated the comparability by practically all studied parameters after a 2-week administration of the domestic analogue. Key words: Cyclosporine A, efficacy, safety, immunosuppression, kidney transplantation. (Pediatric Pharmacology. - 2010; 7(5):82-87)